The Role of Surgical Expertise and Surgical Access in Retroperitoneal Sarcoma Resection – A Retrospective Study - Aeschbacher, P.; Kollár, A.; Candinas, D.; Beldi, G.; Lachenmayer, A. (Frontiers in Surgery, 2022)
Background: Retroperitoneal sarcoma (RPS) is a rare disease often requiring multi-visceral and wide margin resections for which a resection in a sarcoma center is advised. Midline incision seems to be the access of choice. However, up to now there is no evidence for the best surgical access. This study aimed to analyze the oncological outcome according to the surgical expertise and also the incision used for the resection. Methods: All patients treated for RPS between 2007 and 2018 at the Department of Visceral Surgery and Medicine of the University Hospital Bern and receiving a RPS resection in curative intent were included. Patient- and treatment specific factors as well as local recurrence-free survival was analyzed in correlation to the hospital type where the resection occurred. Results: Thirty-five patients were treated for RPS at our center. The majority received their primary RPS resection at a sarcoma center (SC=23) the rest of the resection were performed in a non-sarcoma center (non-SC=12). Median tumor size was 24 cm. Resections were performed via a midline laparotomy (ML=31) or flank incision (FI=4). All patients with a primary FI (n=4) were operated in a non-SC (p=0.003). No patient operated at a non-SC received a multivisceral resection (p=0.004). Incomplete resection (R2) was observed more often when resection was done in a non-SC (p=0.013). Resection at a non-SC was significantly associated with worse recurrence-free survival and disease-free survival after R0/1 resection (2 vs 17 months; Log Rank p value =0.02 respectively 2 vs 15 months; Log Rank p value <0.001). Conclusions: Resection at a non-SC is associated with more incomplete resection and worse outcome in RPS surgery. Inadequate access, such as FI, may prevent complete resection and multivisceral resection if indicated and demonstrates the importance of surgical expertise in the outcome of RPS resection.